2007
DOI: 10.1021/ja075417k
|View full text |Cite
|
Sign up to set email alerts
|

Manganese- or Iron-Catalyzed Homocoupling of Grignard Reagents Using Atmospheric Oxygen as an Oxidant

Abstract: Atmospheric oxygen was used for the first time as an oxidant in metal-catalyzed homocoupling of Grignard reagents. These manganese- or iron-catalyzed reactions are efficient, cheap, and eco-friendly. They are applicable to the large-scale synthesis of symmetrical conjugated compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
130
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(138 citation statements)
references
References 10 publications
3
130
0
5
Order By: Relevance
“…www.chemeurj.org species is unlikely since the reaction occurred with similar yields in the presence of air [15] or acetic anhydride. [16] However, a radical pathway based on single-electron transfer (SET) cannot be ruled out.…”
Section: Entrymentioning
confidence: 99%
“…www.chemeurj.org species is unlikely since the reaction occurred with similar yields in the presence of air [15] or acetic anhydride. [16] However, a radical pathway based on single-electron transfer (SET) cannot be ruled out.…”
Section: Entrymentioning
confidence: 99%
“…Therefore, as the reaction proceeds in the presence of Mn powder, we First, we showed that the reaction is not affected by the presence of air as oxidant since it is well known oxidants provoke the homocoupling of RÀMn derivatives. [10] Whatever the experimental conditions used (inert atmosphere or in air), reactions led to the same result in terms of kinetics and conversion yields. Second evidence was given when the reaction was run in the presence of acetic anhydride [17] since no ketone was produced.…”
mentioning
confidence: 92%
“…[1g] Conversely, symmetrical biaryls can also be synthesized by oxidative homocoupling of nucleophilic organometallic aryl derivatives ArM in the presence of an oxidant. This reaction which, in most cases, is catalyzed by palladium complexes [3g-6] was also developed with other metals such as nickel, [7] copper, [8] iron, [9] manganese, [10] gold [11] and cobalt. [12] Recently, the "transition-metal-free" homocoupling reaction of organomagnesium compounds has also been developed in the presence of a stoichiometric amount of an organic oxidant.…”
mentioning
confidence: 99%
“…Some base free Cumediated alkyne homocoupling reaction, have also been reported [14], and even neat processes have also been developed for oxidative homocoupling reaction of terminal alkynes [15]. The use of transition metals mediated homocoupling reactions other than Pd and Cu for the synthesis of 1, 3-diynes are still limited [16]. During the last decade gold salt and its complexes have played an emerging role for activation of C-C multiple bonds toward a variety of nucleophiles [17].…”
Section: Introductionmentioning
confidence: 99%